Keunikan Penyajian Silek Pangian Rantau Batanghari di Jorong Kampung Surau Kenagarian Gunung Selasih - Tuttriana Tuttriana; Indrayuda Indrayuda (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe and find out the uniqueness of Silek Pangian Rantau Batanghari in Jorong, Surau Village, Kenagarian Gunung Selasih, Pulau Punjung District, Dharmasraya Regency. This type of research is qualitative research using descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, conservation, interviews and documentation. The steps of analyzing data are collecting data, educating data, presenting data and drawing conclusions. The results of the study that Silek Pangian is a silek that entered Jorong Kampung Surau in the 1950s and was displayed at a trustful pilgrimage event at Laman Tuo Sungai Dareh. The uniqueness of Silek Pangian's presentation lies in its soft and vigorous but deadly movements by taking moves in a soft way. The elements and presentation of Silek Pangian are as follows: (1) consists of Salam, Step Ampek, Sembek, pitaluang, Tikam, Pangka Dahan, Ujuang dahan, Sambuik Lantiang (2) Floor Design (3) Music Accompaniment namely Talempong Pacik 4) 2 players (5) The costumes used are black Taluak Balango shirts, black silek pants, black peci, and a torn cloth tied to the player's waist. (6) outdoor performance venues or fields.